2008
DOI: 10.1097/coc.0b013e31816d915f
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue and Functional Dependence in Older Cancer Patients

Abstract: Fatigue is a common chronic problem for older cancer patients and may represent a major cause of functional dependence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
1
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(52 citation statements)
references
References 36 publications
0
45
1
6
Order By: Relevance
“…The mean/ median age of participants ranged from 38 to 78 years. There were few studies of older cancer patients; only four reported a mean/median age greater than 65 years of age [16,46,52,62].…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The mean/ median age of participants ranged from 38 to 78 years. There were few studies of older cancer patients; only four reported a mean/median age greater than 65 years of age [16,46,52,62].…”
Section: Resultsmentioning
confidence: 96%
“…Jacobsen et al [39] Interference Jacobsen et al [40] Interference Interference score range=0.92-0.94 Stein et al [21] Interference Interference score=0.95 Andrykowski et al [42] Interference Interference score=0.95 Booth-Jones et al [43] Interference Dahn et al [44] interference Passik and Kirsh [45] Sum of severity, frequency, interference Wilson et al [46] Interference Hartvig et al [47] Mean of severity, one frequency item, interference Hartvig et al [48] Mean of severity, one frequency item, interference Losito et al [50] Interference Monk et al [51] Interference Shun et al [51] Sum of severity, frequency, interference Sum of severity, frequency, interference=0.92 Siegel et al [52] Interference Temel et al [53] Mean of 4 severity items Young and White [54] Interference Cohen and Fried [55] Mean of severity, frequency, interference Interference score range=0.91-0.93; alpha for sum not reported Donovan et al [56] Mean of 4 severity items 4-item severity score range=0.91-0.93 Jacobsen et al [58] Interference Karvinen et al [59] Interference Lai et al [60] Interference Interference score range=0.92-0.96 Shun et al [61] Sum of severity, frequency, interference Sum of severity, frequency, interference range=0.92-0.95 Donovan et al [20] Mean of 3 severity items Mean of average, most, least=0.84 Espie et al [64] Interference Luciani et al [66] Interference Rogers et al [67] Interference Simonelli et al [68] Interference Interference score=0.94 Yang et al [69] Interference combined with 3 other measures to create symptom stress score Interference score=0.93…”
Section: Reliabilitymentioning
confidence: 98%
“…9 Overall, in patients with cancer, symptoms such as weight loss, fatigue, and physical performance impairment are common, resulting in functional decline, impaired quality of life, and increased health-care costs. [10][11][12] Adult survivors of cancer are at least twice as likely as other adults to report limitations in their ability to perform at least 1 of the activities necessary for daily self-care, such as feeding, bathing, or dressing (ie, activities of daily living [ADL]), or their ability to perform at least 1 of the activities necessary for living independently, such as shopping, preparing meals, doing light housework, or taking medications (ie, instrumental activities of daily living [IADL]). Importantly, functional limitations impair their ability to work outside the home, 13 even in long-term survivors (>5 years).…”
mentioning
confidence: 98%
“…So können die häufig auftretenden, zum Teil reversiblen Folgen einer Chemotherapie (unter anderem kognitive Einschränkungen und Fatigue) bei älte-ren Patienten noch gravierender sein, gerade wenn bereits kognitive Einschrän-kungen vorhanden sind [54]. Eine Studie bei Krebspatienten, die 70 Jahre und älter waren, zeigte, dass über 80% von ihnen an Fatigue litten und dass diese eine lang anhaltende Komplikation der Erkrankung und Behandlung darstellte, die eine Reihe funktioneller Verschlechterungen nach sich zog [56].…”
Section: Wirksamkeit Der Behandlung Nebenwirkungen Und Behandlungsveunclassified